MASYARAKAT PALEMBANG DI TENGAH PEMBANGUNAN LIGHT RAIL TRANSIT (LRT) (Analisis Wacana Kritis Kapitalisme, Sosialisme dan Nasionalisme Dalam Etika Islam) - Sumarni Bayu Anita (Jurnal Dakwah Tabligh, 2017)
Since the construction of Light Rail Transit (LRT) in the city of Palembang, almost all mass media in this bustling city making it as the main topics. Since the beginning of construction of LRT in early December 2015, one of the major newspapers in South Sumatra, Sumatera Ekspres (Sumatera Ekspres Online) also made the news about LRT construction in Palembang as the discussion that never run out of stories. Construction of social reality world LRT near the commodification of pride as well as complaints and it continued to come and go. The contributions of media in raising, framing, and discoursing, it was no doubt of providing significant input in the minds of readers, viewers, or listeners. From here, the information about the construction of LRT was studied through the analysis of the social construction of reality and it based on the theory of social construction from Berger and Luckmann. From this analysis, it was that through social interaction dialectic of the three forms of reality. It called obtained concepts, ie, objective reality, symbolic reality, and subjective reality. The informations of the construction of LRT in Palembang contributed to the moral duty of the media personnel in implementing ethics communication especially in Islam ethics. The messages are delivered not just a phenomenon, but as an icon of social construction of meaning that had been there in the community. LRT construction is part of a combination of capitalism, socialism and nationalism of this country, this time it starting from the provinces that are in the middle of the island of Sumatra, South Sumatra, especially in urban areas, the city of Palembang.